2011
DOI: 10.7205/milmed-d-10-00329
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioners as Primary Care Providers Within the VA

Abstract: We examined the perceptions of nurse practitioners (NPs) and physicians regarding NPs' roles as primary care providers within the Department of Veterans Affairs, thus suggesting possible reasons for the variation of NPs use. NPs and physicians from 7 Veterans Affairs hospitals were surveyed regarding perceptions and concerns about NPs' responsibilities. Quality of care was verified through outpatient services, laboratory results, and medications prescribed for 104,226 hypertensive or diabetic patients. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…NPs perceived, more than MPs, that they could perform tasks autonomously [62,75]. Some MPs stated that NPs require regular MP supervision [62] and that NPs care for patients who are too complex for the NPs’ skills and knowledge [68].…”
Section: Resultsmentioning
confidence: 99%
“…NPs perceived, more than MPs, that they could perform tasks autonomously [62,75]. Some MPs stated that NPs require regular MP supervision [62] and that NPs care for patients who are too complex for the NPs’ skills and knowledge [68].…”
Section: Resultsmentioning
confidence: 99%
“…As the largest fully integrated healthcare system in the US, the VHA had 8.8 million veterans enrolled and 703,500 inpatient admissions in 2012 . Although this makes the VHA an ideal environment to study the role of APPs, few studies have done so . Although studies have compared NPs and PAs to physicians, very little is known about how NPs differ from PAs when practicing in the same environment.…”
mentioning
confidence: 99%
“…14 Although this makes the VHA an ideal environment to study the role of APPs, few studies have done so. 13,[15][16][17][18][19] Although studies have compared NPs and PAs to physicians, very little is known about how NPs differ from PAs when practicing in the same environment.…”
mentioning
confidence: 99%
“…An analysis of administrative primary care data between the years of 2005 and 2010 identified that 19.2% of primary care visits in the VHA were conducted by NPs (Morgan et al., ). Evidence suggests that consistent with non‐VHA studies, chronic care outcomes among veterans with NP‐provided care are similar to those of physician colleagues (Fletcher, Copeland, Lowery, & Reeves, ; Liu, Finkelstein, & Poghosyan, ; McCleery, Christensen, Peterson, Humphrey, & Helfand, ; Mundinger et al., ; Poghosyan, Boyd, & Knutson, ). A secondary data analysis of the Survey of Healthcare Experiences of Patients (SHEP) among veterans between the years 2002 and 2006 suggests that an increase in the number of NPs in a Veteran Integrated Service Network (VISN) can contribute to a statistically significant increase in veteran patient satisfaction with healthcare services.…”
Section: The Np Role In Primary Care At the Vhamentioning
confidence: 57%